Ahmad Tohari’s The dancer: Revisited - Dwi Setiawan (kata, 2017)
As with many post-colonial countries, Indonesia has suffered from a long conflict between the military and civil society since its independence in 1945. This struggle is reflected in Ahmad Tohari’s novel entitled The dancer (2012), which has been largely credited as being critical towards the military regime. Using the theories of depoliticisation, I argue that the novel is 1) largely supportive of the military regime due to the oppressive situation as well as the author’s own political line, and 2) influenced by other powers besides the government. The fact that the novel dares to touch the once suppressed subjects of the Indonesian Communist Party (the arch enemy of the regime) and the anti-communist persecution shows a drive for politicisation. Nevertheless, further analysis shows that, by portraying it as highly political, The dancer actually depoliticises the party in that it only reinforces what has been said of the party and removes any alternative points of view. It also represses and depoliticises the military’s persecution and killing of the suspected communists through the pretexts of self-defence, ignorance, and guilt.